Predictors of powerhouse: a perspective of mitochondrial biomarkers in type 2 diabetes - Muñoz-Úbeda, Mónica; Dash, Surjya Narayan (Frontiers in Endocrinology, 2025)
Mitochondria play a critical role in maintaining the metabolic balance of the cell. The onset and progression of diabetes have been linked to mitochondrial dysfunction, leading to oxidative stress and dysregulation of metabolic intermediates, ultimately leading to a loss of energy production. Mitochondria play a crucial role in glucose stimulated-insulin secretion in pancreatic β-cells and oxidative phosphorylation in beta cells and skeletal muscles. In type-2 diabetes, impaired oxidative phosphorylation and insulin release is linked to insulin resistance (IR). Given the possible involvement of mitochondrial activity in the pathophysiology of diabetes, it would be highly desirable to investigate possible biomarkers or indicators that may provide details on the onset, severity or progression of the disease. The use of biomarkers is essential both for the diagnosis of mitochondrial diseases and for monitoring their metabolic status. The discovery and characterization of numerous biomarkers that correlate with mitochondrial diseases has led to the development of a number of new biomarkers. Biomarkers associated with human mitochondrial dysfunction are critical for the development of targeted therapies and early diagnosis of diabetes. Based on an investigation of the literature, this perspective outlines the state of knowledge on mitochondrial biomarkers and examines the data supporting their application in the early diagnosis, prognosis, and monitoring of diabetes.